CircRNA ITCH: Insight Into Its Role and Clinical Application Prospect in Tumor and Non-Tumor Diseases - Liu, Tong; Huang, Tao; Shang, Mei; Han, Gang (Frontiers in Genetics, 2022)
CircRNA E3 ubiquitin protein ligase (ITCH) (circRNA ITCH, circ-ITCH), a stable closed-loop RNA derived from the 20q11.22 region of chromosome 20, is a new circRNA discovered in the cytoplasm in recent decades. Studies have shown that it does not encode proteins, but regulates proteins expression at different levels. It is down-regulated in tumor diseases and is involved in a number of biological activities, including inhibiting cell proliferation, migration, invasion, and promoting apoptosis. It can also alter disease progression in non-tumor disease by affecting the cell cycle, inflammatory response, and critical proteins. Circ-ITCH also holds a lot of promise in terms of tumor and non-tumor clinical diagnosis, prognosis, and targeted therapy. As a result, in order to aid clinical research in the hunt for a new strategy for diagnosing and treating human diseases, this study describes the mechanism of circ-ITCH as well as its clinical implications.